Innovation in nursing practice and education - Argyropoulos, Theodoros; Chronopoulou, Ioanna (Health & Research Journal, 2021)
Abstract Background: Innovation is defined as "the applied use of knowledge for the production and provision of new or substantially improved products, processes or services that find direct productive, utilitarian or commercial application. Innovations in healthcare fall under the broader umbrella of social innovations. Aim: The presentation of innovation in the field of nursing science and the promotion of its beneficial role in the development of nursing practice and in the improvement of the care provided. Material and method: A literature review was conducted in online databases (Google Scholar, PubMed) with appropriate indexing words. Articles published in Greek or English language were sought, in reputable journals with a publication date after 2000. Results: In nursing, as in science and art, there are both elements of product innovations and elements of process-related innovations. Innovation in nursing science is widespread with the direct effect of improving nursing practice, patient experiences and providing care. Conclusions: By proposing and implementing innovations in nursing science, important results are achieved such as modern concepts, new knowledge and skills, scientific recognition of nurses, the formation of a different work culture as well as higher incomes. The nurse leader forms a working culture of innovations, encourages nurses in continuing education, facilitates the development of innovations and actively participates.